2018
DOI: 10.1245/s10434-018-6560-0
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Surgical and Chemotherapeutic Treatments of Goblet Cell Carcinoid Tumors of the Appendix

Abstract: In this population-based cohort, we demonstrate excellent survival outcomes in stage I-III appendiceal GCCs and clinical appendicitis. Hemicolectomy remains the standard treatment. In metastatic disease, outcomes remain poor, although MOR ± HIPEC may improve survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 17 publications
2
19
0
Order By: Relevance
“…In our cohort, only 41.4% of patients with Stage III disease and 70.2% of patients with Stage IV disease underwent chemotherapy. This is similar to a recent study, which showed that 62.5% of Stage IV patients received adjuvant chemotherapy . In this study, there was significantly improved survival for patients with Stage III disease undergoing chemotherapy.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In our cohort, only 41.4% of patients with Stage III disease and 70.2% of patients with Stage IV disease underwent chemotherapy. This is similar to a recent study, which showed that 62.5% of Stage IV patients received adjuvant chemotherapy . In this study, there was significantly improved survival for patients with Stage III disease undergoing chemotherapy.…”
Section: Discussionsupporting
confidence: 92%
“…In terms of independent predictors of survival, older age, the presence of metastatic disease, and positive surgical margins were associated with decreased overall survival. Prior studies have linked lymph node metastasis and distant metastatic disease to overall survival . Interestingly, tumor size was not predictive of overall survival, which is consistent with prior reports evaluating GCC, but in contrast to studies of other carcinoid tumors, thus adding further evidence that GCCs are a distinct pathologic disease from other hindgut neuroendocrine tumors …”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…71 This together with other smaller studies have shown that CRS with HIPEC may be considered for select patients with peritoneal metastases from GCA. 68,72,73…”
Section: Goblet Cell Adenocarcinoma/mixed Adenoneuroendocrine Carcinomamentioning
confidence: 99%
“…9 However, at present, the evidence for CRS-HIPEC as treatment for PM of GCCs and MANECs is unclear and the current literature on this subject consists of relatively small, noncomparative, retrospective cohort studies presenting heterogeneous outcomes. 2,3,10,11 The lack of evidence to support this multimodality approach stresses the importance of evaluating its value in a well-defined cohort of GCC and MANEC patients. Therefore, the aims of the present study were: (1) to present available evidence in a systematic review of the literature and (2) to compare clinical outcomes of GCC and MANEC patients with PM treated with CRS-HIPEC to patients that underwent surgery without HIPEC using an international multicenter cohort together with a nationwide cancer database.…”
Section: Introductionmentioning
confidence: 99%